2018
DOI: 10.1371/journal.pone.0201898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age at initiation of antiretroviral therapy on treatment outcomes; A retrospective cohort study at a large HIV clinic in southwestern Uganda

Abstract: BackgroundThe prevalence of HIV infection among older persons is increasing yet older age at initiation of antiretroviral therapy (ART) may be associated with poorer treatment outcomes including mortality. However, majority of these studies have been done in the western world and there is limited data in resource limited settings. Our study used routinely collected health facility data to assess trends in age at initiation of ART, the effect of age at ART initiation on mortality and immunological response at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“… Liu et al, (2011) [ 20 ] Retrospective cohort 2004–2009 7 8271 11,927 (65.3) 1673 (9.2) Hgb and MUAC 17. Ssebutinde et al, (2018) [ 35 ] Retrospective cohort 2006–2012 7 8364 5308 (63.5) 180 (2.1) Age, sex, WHO staging, CD4 count, and level of education 18. Maskew et al, (2013) Retrospective cohort 2004–2010 8 7354 4621 (62.8) 333 (4.5) Sex, age, CD4 count, and Hgb 19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Liu et al, (2011) [ 20 ] Retrospective cohort 2004–2009 7 8271 11,927 (65.3) 1673 (9.2) Hgb and MUAC 17. Ssebutinde et al, (2018) [ 35 ] Retrospective cohort 2006–2012 7 8364 5308 (63.5) 180 (2.1) Age, sex, WHO staging, CD4 count, and level of education 18. Maskew et al, (2013) Retrospective cohort 2004–2010 8 7354 4621 (62.8) 333 (4.5) Sex, age, CD4 count, and Hgb 19.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 23 studies included in the meta-analysis, 17 studies showed that undernutrition has a significant effect on mortality in adults living with HIV [ 18 , 21 , 24 , 25 , 27 31 , 34 , 101 , 105 , 106 , 110 , 111 ]. However, six studies reported that undernutrition has no significant effect on mortality in this population [ 19 , 35 , 37 – 39 , 99 ]. Finally, the pooled AHR of 23 cohort studies involving 125,790 individuals showed that undernourished adults living with HIV were two-fold (AHR: 2.1, 95% CI: 1.8, 2.4) more likely to die as compared to their well-nourished counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…9 Ssebutinde et al observed an overall increased risk of decline in the CD4 cell count in the older age group following treatment' however, this was not identified as statistically significant. 11 . This was the first study to include patients on an INSTI-based regimen, although it was a small percentage.…”
Section: Discussionmentioning
confidence: 99%
“…observed an overall increased risk of decline in the CD4 cell count in the older age group following treatment’ however, this was not identified as statistically significant. 11 A study by Sabin et al. included pediatric and adult patients as part of an observational multicohort study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation